Body mass index changes and predictors among adults living with HIV/AIDS who are on anti-retroviral therapy at Chiro General Hospital, Eastern Ethiopia: a facility-based retrospective cohort study - Sintayehu Amsalu; Tara Wilfong; Sewmehon Amsalu; Abdu Oumer; Berhe Gebremichael (BMC Nutrition)
Abstract Background Human immunodeficiency virus continues to be a major global public health issue. Body mass index is a general indicator of nutritional status and has emerged as a powerful predictor of morbidity and mortality among adult PLHIV initiating antiretroviral therapy in resource-limited settings. However, there is a dearth of information regarding longitudinal changes in body mass index and its predictors among adult PLHIV in Ethiopia, particularly in the study area. This study aimed to assess body mass index changes and their predictors among adults living with HIV/AIDS who were receiving on antiretroviral therapy at Chiro General Hospital, Eastern Ethiopia from August 15, 2023 to September 30, 2023. Methods A Facility-based retrospective cohort study was implemented among 1049 randomly selected charts of adults living with HIV/AIDS. The data were collected by reviewing charts of clients and antiretroviral therapy registers. The data were entered into Epi data statistical software version 4.6 and exported to SPSS version 25 for analysis. Descriptive statistics were used to describe the characteristics of the patients. A linear mixed effect model was used to identify the predictors of body mass index change. A P value of less than 0.05 was considered statistically significant. Results Generally, in this study patients presented a linear increase in the mean BMI from 19 kg/m2 baseline to 21.2 kg/m2 at the 5th year of follow up. Moreover, the following variables were identified as independent predictors of BMI change: age (β = 0.58, 95% CI; 0.043, 0.072), marital status (β = -0.275, 95% CI: -0.457,-0.093 ), advanced WHO stage (β = -0.496, 95% CI: -0.548, -0.443 ), CD4 count (β = 0.001, 95% CI: 0.001, 0.001), duration of antiretroviral therapy (β = 0.005, 95% CI: 0.001,0.009), time of follow up (β = 0.205, 95% CI: 0.198,0.212), no ART shift (β = -0.844, 95% CI: -1.135, -0.552), no CPT (β = 0.591, 95% CI: 0.365,0.817), urban residence (β = 0.767, 95% CI:0.401,1.132) and good adherence to ART (β = 0.975, CI:0.302, 1.649). Conclusion There was a significant improvement in the mean BMI over time and a reduction in the rate of undernutrition during the follow-up period.